Electromagnetic fields exposure assessment among workers at broadcast centers in Poland - Piotr Politański; Halina Aniołczyk; Elżbieta Gadzicka; Alicja Bortkiewicz; Marek Zmyślony (Nofer Institute of Occupational Medicine, 2018)
Background In the studies investigating the potential health effects of occupational exposure to electromagnetic fields (EMF), the key problem is the assessment of workers' exposure. Electromagnetic fields exposure assessment requires determining maximum EMF levels, for the acute effect, and the dose absorbed, for the cumulative effect. A study was undertaken to determine EMF exposure in workers at broadcasting centers (BCs) in Poland. It was the first part of a comprehensive project on health effects of occupational exposure to EMF. Material and Methods The study was conducted in 4 selected BCs. Spot measurements of electric field strength (E), and the results of E measurements that were made in the past for occupational hygiene assessments, were used for determining workers' exposure to electric field. The parameters considered were the maximum E value (E max ), the weighted average E value (E avg ) and the E lifetime dose (E lifetime dose ). Results In the group of workers examined, the E values did not exceed 16.7 V/m for Emax (the occupational exposure limit (OEL) for work shift in Poland is 20 V/m), 2.9 V/m for E avg and 1 500 000 (V/m) 2 ×h for E lifetime dose . Conclusions In view of the lack of dosimetry data, a retrospective assessment of BC workers' exposure to very high frequency and ultra-high frequency EMF was conducted, which made it possible to estimate EMF lifetime dose for the workers. Since the EMF exposure levels at BCs did not exceed the admissible values, they can be considered safe to the workers' health, according to the approach used for developing OELs for EMF exposure. Med Pr 2018;69(5):477-482